Neither Worker, Nor Queen: An Ant Caste Specialized in the Production of Unfertilized Eggs - J. Heinze; S. P. Cover; B. Hölldobler (Psyche: A Journal of Entomology)
In addition to a queen and workers, colonies of the ant Crematogaster smithi Creighton from Chiricahua Mountains, Arizona, may contain one or several conspicuous “large workers” whose size, external morphology, and number of ovarioles are intermediate between that of queens on one side and that of workers on the other. According to laboratory observations, “large workers” are specialized for the production of unfertilized eggs, which are mainly eaten by the larvae and the queen but may develop into males in queenless colonies. We describe the morphology and the behavior of “large workers” and discuss their evolutionary significance.